Adrenal insufficiency in patients with stable non-cystic fibrosis bronchiectasis - Rajagopala, Srinivas (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND & OBJECTIVES: Suppressed adrenal responses associated with inhaled steroid use have been reported in patients with bronchiectasis and have been shown to be associated with poor quality of life. This study was undertaken to examine the prevalence of suppressed cortisol responses in stable bronchiectasis and determine their correlation with the use of inhaled corticosteroids, radiologic severity of bronchiectasis and quality of life (QOL) scores. METHODS: In this case-control study, cases were patients with bronchiectasis and suppressed cortisol responses and controls were healthy volunteers, and patients with bronchiectasis without suppressed cortisol responses. Symptoms, lung function test values, exercise capacity, HRCT severity scores for bronchiectasis, exacerbations, inhaled corticosteroid use and quality of life scores were compared between patients with and without suppressed cortisol values. RESULTS: Forty consecutive patients with bronchiectasis and 40 matched controls underwent 1-μg cosyntropin testing. Baseline cortisol (mean difference -2.0 μg/dl, P=0.04) and 30-minute stimulated cortisol (mean difference -3.73 μg/dl, P=0.001) were significantly lower in patients with bronchiectasis. One patient had absolute adrenal insufficiency and 39.5 per cent (15/38) patients with bronchiectasis had impaired stimulated responses. Baseline and stimulated cortisol responses were unaffected by inhaled steroids (O.R 1.03, P=0.96). SGRQ scores were negatively correlated with body mass (r= -0.51, P=0.001) and bronchiectasis severity (r=0.37, P=0.019), but not related to baseline or stimulated cortisol responses. INTERPRETATION & CONCLUSIONS: Our results showed that the impaired adrenal responses to 1-μg cosyntropin were common in patients with bronchiectasis. This was not associated with the use of inhaled steroids or severity of bronchiectasis. Poor health status was associated with advanced disease and not with cortisol responses to the 1-μg cosyntropin test.